Estimation of the volume of sea ice cover in the Sea of Okhotsk and related atmospheric conditions for 1991/92-1998/99 winters - タテヤマ, カズタカ; エノモト, ヒロユキ; Tateyama, Kazutaka; Enomoto, Hiroyuki (National Institute of Polar Research, 2000)
P(論文) The volume of sea ice cover in the Sea of Okhotsk during 1991/92-1998/99 winters (December-April) was estimated by using SSM/I data sets with the S/KIT algorithm (Tateyama et al., Bull. Glaciol. Res., 17,23,2000) which can distinguish among fast ice, floes, young ice, new ice and multi-year ice types. The variability in the yearly ice production is discussed in association with daily mean air temperature and winter mean sea level pressure. Areas of less ice appeared in the winters of 1995/96 and 1996/97,during which ice cover was 75% and 69%, respectively, of the maximum ice area (1.25×10^6km^2) in the winter of 1997/98. The ice volumes in the winters of 1995/96 and 1996/97 decreased by as much as 58% and 56%, respectively, of the maximum ice volume (5.5×10^2km^3) in 1994/95. Furthermore, the mean ice thickness, calculated by dividing the ice volume by ice area of the whole Okhotsk Sea, was thinner in winters when the ice area was small. The ice volume was correlated with cold air conditions, especially off the northeast coast of Kamchatka, where air temperature is affected greatly by the Aleutian low. The winter mean sea level pressure showed that ice volume was small when the Aleutian low was strong. departmental bulletin paper